Workshop on Information Technology Education in the Implementation of Independent Learning at Merdeka Campus - Kusumaryono, R. Suyato; Ilham, Saeful; Huda, Nurul; Farhas Thoriq, Iqbal (RISTEC : Research in Information Systems and Technology, 2022)
This study aims to obtain a clear picture of the Information Technology Education Workshop in the Implementation of Independent Learning on the Independent Campus which was held on Thursday - Saturday, July 14 to 16, 2022 at SMA Ma'arif Banyuresmi Garut. This study uses a qualitative approach, the type of research in this study is descriptive with survey techniques. The data collection technique used is a questionnaire. The results of this study use a description of the implementation of the Information Technology Education Workshop in the Implementation of Independent Learning at the Merdeka Campus based on the planning, implementation, and evaluation of learning. In order for the learning process to run well, at the time of planning, the facilitator involves students to formulate the objectives of the workshop implementation.